Changes and the principle of assessment of readiness for changes in the life cycle of buildings - D. A. Khrustalev (Vestnik MGSU)
Introduction. The subject of this study is volumetric and spatial elements of a building and their locations. Practical significance of the study is to accelerate decision making in the selection of properties for further practical work of arrangement. The purpose of the study is to find the possibility of comprehensive evaluation of architectural solutions for hypothetical changes, such as functional purpose. Scientific novelty: the possibility of simplifying prospective changes at the design stage is considered.Materials and methods. The spectrum of changes to buildings over time is described – from operational needs, through renovations to major renovations. The basis of the work is rich in frequent changes material on buildings for research and risky innovation. A range of changes, statistically frequently occurring in civil engineering buildings, is presented. Empirical and theoretical research methods have been used in an integrated way.Results. A list of the techniques is given which the architect can use to facilitate possible future changes in a building or premises, related to a change of activity, a change of tenant or owner. The characteristics of the parties involved in considering each of the features of the property are described. Two simplified examples are used to assess the architectural solutions affecting the possibility of future changes. An assessment package for determining a building’s readiness for prospective change, using office-type ordinal diagrams, is given.Conclusions. The appraisal apparatus can be used to compare properties that are to be converted (due to sale or rent). The application of the presented appraisal apparatus will require the creation of a mathematical formula that takes into account the significant database for each of the properties. The result of the appraisal is a summary in numerical form and a diagram reflecting the architectural solution, showing the building’s readiness for future changes.